Myocardial bridges in bovine of the Canchim race, I - Microscopic aspects - Santos, José Wilson dos; Bombonato, Pedro Primo; Beletti, Marcelo Emílio; Severino, Renato Souto; Carneiro e Silva, Frederico Ozanan (Brazilian Journal of Veterinary Research and Animal Science, 2000)
Thirty hearts of female Bos taurus bovines of Canchin breed were studied, the relationship between the arterial wall and the tissues surrounding different drawbridge segments was also assessed. Tissue fragments were collected and treated according to conventional microscopic techniques. Muscle fibers of the pre-bridge and post-bridge segments were of subepicardiac in location. The striate cardiac muscle fibers of the bridging segment are predominantly oblique to the vase, accompanying its longitudinal axis; they separate themselves to form a losanged space to shelter in its center the coronary artery and at its laterals the conjunctive tissue, constituted by colagens and elastic fibers, vases, nerves and adipose tissue